Prognostic relevance of the proximal resection margin distance in distal gastrectomy for gastric adenocarcinoma - Rompen, Ingmar F.; Schütte, Isabel; Crnovrsanin, Nerma; Schiefer, Sabine; Billeter, Adrian; Haag, Georg Martin; Longerich, Thomas; Czigány, Zoltán; Schmidt, Thomas; Billmann, Franck; Peters, Leila; Nienhüser, Henrik (Annals of surgical oncology, 2024)
Background: The risk for recurrence in patients with distal gastric cancer can be reduced by surgical radicality. However, dispute exists about the value of the proposed minimum proximal margin distance (PMD). Here, we assess the prognostic value of the safety distance between the proximal resection margin and the tumor. Patients and Methods: This is a single-center cohort study of patients undergoing distal gastrectomy for gastric adenocarcinoma (2001–2021). Cohorts were defined by adequacy of the PMD according to the European Society for Medical Oncology (ESMO) guidelines (≥ 5 cm for intestinal and ≥ 8 cm for diffuse Laurén’s subtypes). Overall survival (OS) and time to progression (TTP) were assessed by log-rank and multivariable Cox-regression analyses. Results: Of 176 patients, 70 (39.8%) had a sufficient PMD. An adequate PMD was associated with cancer of the intestinal subtype (67% vs. 45%, p = 0.010). Estimated 5-year survival was 63% [95% confidence interval (CI) 51–78] and 62% (95% CI 53–73) for adequate and inadequate PMD, respectively. Overall, an adequate PMD was not prognostic for OS (HR 0.81, 95% CI 0.48–1.38) in the multivariable analysis. However, in patients with diffuse subtype, an adequate PMD was associated with improved oncological outcomes (median OS not reached versus 131 months, p = 0.038, median TTP not reached versus 88.0 months, p = 0.003). Conclusion: Patients with diffuse gastric cancer are at greater risk to undergo resection with an inadequate PMD, which in those patients is associated with worse oncological outcomes. For the intestinal subtype, there was no prognostic association with PMD, indicating that a distal gastrectomy with partial preservation of the gastric function may also be feasible in the setting where an extensive PMD is not achievable.
Gesehen am 03.01.2025